Utilization of waste plastic bottles in asphalt mixture - Moghaddam, T.B.; Karim, M.R.; Soltani, M. (2013)
Nowadays, large amounts of waste materials are being produced in the world. One of the waste materials is plastic bottle. Generating disposable plastic bottles is becoming a major problem in many countries. Using waste plastic as a secondary material in construction projects would be a solution to overcome the crisis of producing large amount of waste plastics in one hand and improving the structure's characteristics such as resistance against cracking on the other hand. This study aimed to investigate the effects of adding plastic bottles in road pavement. Marshall properties as well as specific gravity of asphalt mixture containing different percentages of plastic bottles were evaluated. Besides, Optimum Asphalt Content (OAC) was calculated for each percentages of plastic bottles used in the mix. The stiffness and fatigue characteristics of mixture were assessed at OAC value. Results showed that the stability and flow values of asphalt mixture increased by adding waste crushed plastic bottle into the asphalt mixture. Further, it was shown that the bulk specific gravity and stiffness of mixtures increased by adding lower amount of plastic bottles; however, adding higher amounts of plastic resulted in lower specific gravity and mix stiffness. In addition, it was concluded that the mixtures containing waste plastic bottles have lower OAC values compared to the conventional mixture, and this may reduce the amount of asphalt binder can be used in road construction projects. Besides, the mixtures containing waste plastic showed significantly greater fatigue resistance than the conventional mixture.